2017
DOI: 10.1002/anie.201700464
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Analysis of Folding upon Binding of a Disordered Protein by Using Dissolution DNP NMR Spectroscopy

Abstract: The kinase inhibitory domain of the cell cycle regulatory protein p27Kip1 (p27) was nuclear spin hyperpolarized using dissolution dynamic nuclear polarization (D-DNP). While intrinsically disordered in isolation, p27 adopts secondary structure, including α-helical structure, upon binding to cyclin-dependent kinase 2 (Cdk2)/cyclin A. The sensitivity gains obtained with hyperpolarization enable the real-time observation of 13C NMR signals during p27 folding upon binding to Cdk2/cyclin A on a time scale of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
(50 reference statements)
0
25
1
Order By: Relevance
“…This is, to the best of our knowledge, the lowest concentration achieved by high-resolution NMR spectroscopy in liquids, even relative to other hyperpolarization techniques. For instance, Ragavan et al reported detection of 15 and 20 μM proteins via D-DNP (47,48). This is a considerably higher concentration than the one achieved in the present study.…”
Section: Lc-photo-cidnp Depends Only Weakly On Laser Power At Extremelycontrasting
confidence: 67%
“…This is, to the best of our knowledge, the lowest concentration achieved by high-resolution NMR spectroscopy in liquids, even relative to other hyperpolarization techniques. For instance, Ragavan et al reported detection of 15 and 20 μM proteins via D-DNP (47,48). This is a considerably higher concentration than the one achieved in the present study.…”
Section: Lc-photo-cidnp Depends Only Weakly On Laser Power At Extremelycontrasting
confidence: 67%
“…Ragavan et al demonstrated the real‐time observation of 13 C DNP‐enhanced NMR signals during p27 folding upon binding to Cdk2/cyclin A on a time scale of several seconds, providing evidence for a structural change of p27 associated with the interaction with Cdk2/cyclin A . Comparing 13 C NMR spectra of hyperpolarized p27 with and without admixing of Cdk2/cyclin A complex, higher signal intensities of 13 CO groups in samples of hyperpolarized p27 mixed with Cdk2/cyclin A complex was observed, which indicated the formation of α‐helical secondary structures.…”
Section: Applicationsmentioning
confidence: 99%
“…Comparing 13 C NMR spectra of hyperpolarized p27 with and without admixing of Cdk2/cyclin A complex, higher signal intensities of 13 CO groups in samples of hyperpolarized p27 mixed with Cdk2/cyclin A complex was observed, which indicated the formation of α‐helical secondary structures. The series of spectra obtained from samples with and without Cdk2/cyclin A complex was analyzed by fitting intensities of spectra at each chemical shift . From the fit, decay rate constants were obtained.…”
Section: Applicationsmentioning
confidence: 99%
“…This core‐periphery learning hypothesis is novel, since it connects previously fragmented knowledge on the capability of model networks to develop system attractors in learning processes on network periphery‐generated creative innovations and on the differential role of core and periphery nodes in attractor formation in a large variety of real‐world networks . Moreover, the hypothesis expands these lines of evidence to a general adaptation and learning mechanism of complex systems.…”
Section: The Core‐periphery Learning Hypothesis: Known Stimuli Trimentioning
confidence: 90%
“…Disordered segments often fold upon binding to the upstream signaling partner, allowing “conformational signaling” as exemplified by the nuclear hormone receptor family and the cAMP response element‐binding protein (CREB) among many others . Folding of intrinsically disordered segments often occurs in the range of seconds, which is much slower than either the picosec time‐scale of protein core‐mediated signaling, or the nsec to msec timescale of conformational changes …”
Section: Examples Of System Response Duality To Well‐known Versus mentioning
confidence: 99%